2011
DOI: 10.1021/ol200333p
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis-Inspired Intramolecular Oxa-Conjugate Cyclization of α,β-Unsaturated Thioesters: Stereoselective Synthesis of 2,6-cis-Substituted Tetrahydropyrans

Abstract: Intramolecular oxa-conjugate cyclization of α,β-unsaturated thioesters under Brønsted acid catalysis, inspired by biosynthesis of polyketide natural products, provides a variety of 2,6-cis-substituted tetrahydropyran derivatives with excellent diastereoselectivities. An added bonus of this methodology is that the product tetrahydropyrans could be readily elaborated to various derivatives by exploiting the unique reactivity of the thioester group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…aldehyde 4d ), the second step of this tandem sequence, that is, the oxa‐Michael addition, did not take place, and uncyclized alcohol 2db was obtained in 80 % yield (Table 2, entry 3). This was perhaps the result of the low reactivity of the α,β‐unsaturated ester as the conjugate acceptor under the reaction conditions employed 8,11,12. In contrast, aldehyde 4e , bearing a more reactive alkylidine malonate as Michael acceptor, was found to work efficiently, and corresponding cis ‐THP derivative 1eb was formed in good yield with good diastereoselectivity (Table 2, entry 4).…”
Section: Resultsmentioning
confidence: 99%
“…aldehyde 4d ), the second step of this tandem sequence, that is, the oxa‐Michael addition, did not take place, and uncyclized alcohol 2db was obtained in 80 % yield (Table 2, entry 3). This was perhaps the result of the low reactivity of the α,β‐unsaturated ester as the conjugate acceptor under the reaction conditions employed 8,11,12. In contrast, aldehyde 4e , bearing a more reactive alkylidine malonate as Michael acceptor, was found to work efficiently, and corresponding cis ‐THP derivative 1eb was formed in good yield with good diastereoselectivity (Table 2, entry 4).…”
Section: Resultsmentioning
confidence: 99%
“…Chemical IMOMA, often integrated into efficient tandem processes, gained growing attention for the stereoselective synthesis of tetrahydropyrans (THPs) during recent years. It has been shown that the cis - or trans -THP selectivity of IMOMA can be influenced by kinetic or thermodynamic reaction control, by the type of activation (acid, base, or metal catalysis), by the configuration of the double bond, and by the nature of the acceptor moiety. Although the reaction outcome is predictable for some systems (tandem-cross metathesis-IMOMA with vinylketone intermediates for example reliably leads to cis -THPs with diastereomeric excess > 5:1), low to moderate d.e. s are rather common and have only occasionally been improved by extensive reaction optimization or product re-equilibration (see, e.g., refs ).…”
Section: Introductionmentioning
confidence: 99%
“…s are rather common and have only occasionally been improved by extensive reaction optimization or product re-equilibration (see, e.g., refs ). Pioneering studies on the thioester IMOMA have provided valuable insight into the reasons for the high substrate dependence of the cis - trans selectivity, along with the establishment of guidelines for diastereoselective THP cyclization in specific systems. …”
Section: Introductionmentioning
confidence: 99%
“…17 The C20-C32 tetrahydropyran core of the phorboxazoles and the C22 epimer were synthesised in the Clarke group using silyl ether deprotection/oxy-Michael cyclisation as the key step. Fuwa 18 speculated that the replacement of α,β-unsaturated ester Michael acceptor with α,β-unsaturated thioester Michael acceptor may enhance the 2,6-cis-selectivities of THP formation. The Clarke group found that using a Michael cyclisation reaction and a thioester electrophile they could generate either the 2,6-cis-or 2,6-trans-THP unit with excellent selectivities depending on the reaction conditions used.…”
Section: Michael Reactionsmentioning
confidence: 99%